2019
DOI: 10.1111/1744-7917.12697
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about biological nitrogen fixation in insects? Evidence and implications for the insect and the ecosystem

Abstract: Many insects feed on a low-nitrogen diet, and the origin of their nitrogen supply is poorly understood. It has been hypothesized that some insects rely on nitrogen-fixing bacteria (diazotrophs) to supplement their diets. Nitrogen fixation by diazotrophs has been extensively studied and convincingly demonstrated in termites, while evidence for the occurrence and role of nitrogen fixation in the diet of other insects is less conclusive. Here, we summarize the methods to detect nitrogen fixation in insects and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 87 publications
(155 reference statements)
0
37
0
Order By: Relevance
“…Potential diazotrophic microorganisms have already been recovered from different insect orders, such as Coleoptera, Blattodea, Diptera, Hemiptera and Hymenoptera (Behar et al, 2005;Morales-Jiménez et al, 2009;Pinto-Tomás et al, 2009;Bar-Shmuel et al, 2020). Bacteria belonging to the genus Pantoea, for example, have repeatedly been isolated from the leaf-cutting ants symbiosis sampled in different countries, such as Brazil, Argentina and Panama, and have been able to fix nitrogen in the fungus garden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential diazotrophic microorganisms have already been recovered from different insect orders, such as Coleoptera, Blattodea, Diptera, Hemiptera and Hymenoptera (Behar et al, 2005;Morales-Jiménez et al, 2009;Pinto-Tomás et al, 2009;Bar-Shmuel et al, 2020). Bacteria belonging to the genus Pantoea, for example, have repeatedly been isolated from the leaf-cutting ants symbiosis sampled in different countries, such as Brazil, Argentina and Panama, and have been able to fix nitrogen in the fungus garden.…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria genera Pantoea, Rhizobium, Methylobacterium, and Pseudomonas have known diazotrophic potential (Borm et al, 2008;Pinto-Tomás et al, 2009;Ruiz-González et al, 2019;Bar-Shmuel et al, 2020). Due to the significant number of strains isolated from Cecropia-Azteca that could potentially fix nitrogen (22; 56.4%), the nitrogenase activity of these strains was tested.…”
Section: Isolates Growth In Nitrogen-free Mediummentioning
confidence: 99%
“…Plant material is low in nitrogen, specific amino acids, sterols and B vitamins, and in many cases, microorganisms synthesize these components (Dillon & Dillon, 2004). These functions on metabolism processes and nutritional contributions of gut bacteria should be essential in insects living on plants and other suboptimal diets (Bar-Shmuel et al, 2020;Dillon & Dillon, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These were able to recycle uric acid in vitro, used as a nitrogen source for eggs, larvae, and adults (male and female) of the beetle Dendroctonus valens (Morales-Jiménez et al, 2013). The bacterial nitrogen-fixing activity has been reported in insects like termites, cockroaches, ants, aphids, and beetles [see Bar-Shmuel et al (2020)]; however, none of the contributing genera have been reported as nitrogen fixers in insect gut; with exception of the order rhizobiales, which are known for their ability to fix nitrogen in plants (Masson-Boivin et al, 2009).…”
Section: Discussion the Predominance Of Bacterial Groups According Tomentioning
confidence: 99%